2016
DOI: 10.1108/cg-12-2015-0162
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance in China: a review

Abstract: Purpose This study aims to provide a review of corporate governance in China because effective and strong corporate governance is necessary for the efficient functioning and long-term sustainability of financial markets and corporations. Design/methodology/approach The author provides a literature review of corporate governance in China through themes such as the concentration of state ownership, the degree of independence among board directors, insider trading, quality of financial disclosures and the matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 84 publications
0
15
0
4
Order By: Relevance
“…Active intervention by regulatory bodies was necessary to instill good corporate governance which in turn stimulated firm performance. Sabbaghi (2016) indicated that poor corporate governance mechanisms as measured by concentration of state ownership, the degree of independence among board directors, insider trading and quality of financial disclosures among others have a direct association with firm performance. Sabbaghi (2016) also provided insights to policymakers interested in enhancing quality of corporate governance in China.…”
Section: Effects Of Firm's Corporate Governance On Credit Riskmentioning
confidence: 99%
“…Active intervention by regulatory bodies was necessary to instill good corporate governance which in turn stimulated firm performance. Sabbaghi (2016) indicated that poor corporate governance mechanisms as measured by concentration of state ownership, the degree of independence among board directors, insider trading and quality of financial disclosures among others have a direct association with firm performance. Sabbaghi (2016) also provided insights to policymakers interested in enhancing quality of corporate governance in China.…”
Section: Effects Of Firm's Corporate Governance On Credit Riskmentioning
confidence: 99%
“…Due to the increasing public concern regarding corporate frauds, this concept has now become very popular in academia. The principal motive of CG is to control the opportunistic behavior of top level administrators and executives Sabbaghi, 2016), often found involved in corporate scams. CG is the system to direct and control companies' affairs (Abor, 2007;Alabdullah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Another research avenue relates to the antecedents of the incorporation of corporate culture in national corporate governance codes. An important antecedent could be the national culture of the issuing country (Agyei-Mensah, 2017;Alazzani et al, 2017;Azam et al, 2019;Haxhi and Van Ees, 2010;Humphries and Whelan, 2017;Karlsson et al, 2018;Li and Harrison, 2008;Sabbaghi 2016;Schonfelder et al, 2016). Researchers can explore the effects of national culture on the content of national codes in various ways.…”
Section: Avenues For Future Researchmentioning
confidence: 99%